The Effectiveness of Kenikir and Betel Leaves Extract as Bio Fungicide to the Causes of Anthracnose Disease (Colletotrichum Capsici) on Chili Plants (Capsicum annum L.) with In vitro - Maimunah Maimunah; Azwana Azwana; Cornelis Pandala (Budapest International Research and Critics University, 2019)
Effectiveness Kenikir and Betle Leaft Extraction as Biofungicide to Cause Disease Antraknosa (Colletotricum capsici) On Chili (Capsicum annuum) in In vitro. The research was done in the Laboratory Protection Plant Agriculture Faculty University of Medan Area, was held since Mei to July 2018. The research use Design Random Complete (RAL) Non Factorial with treatment F0 = negative control (PDA Media 100 %) F1 = Positive control (Synthetic fungicide 0.2%), F2 = 20% kenikir+ 10%betel, F3 = 30 % kenikir+ 10%betel,, F4 = 40% kenikir+ 10%betel, F5 = 20% kenikir+ 20%betel, F6 = 30 % kenikir+ 20%betel, F7 = 40% kenikir+ 20%betel, F8 = 20% kenikir+ 30%betel, F9 = 30% kenikir+ 30%betel, F10 = 40 % kenikir+ 30%betel. The results of the study: the tested extract of kenikir and betel leaf leaves showed the same results for inhibiting the growth of colony diameter and percentage of fungi growth.